2006
DOI: 10.1128/jb.00507-06
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome Analysis ofTropheryma whippleiin Response to Temperature Stresses

Abstract: Tropheryma whipplei, the agent responsible for Whipple disease, is a poorly known pathogen suspected to have an environmental origin. The availability of the sequence of the 0.92-Mb genome of this organism made a global gene expression analysis in response to thermal stresses feasible, which resulted in unique transcription profiles. A few genes were differentially transcribed after 15 min of exposure at 43°C. The effects observed included up-regulation of the dnaK regulon, which is composed of six genes and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…Homologues of enzymes involved in the utilization of carbohydrates and enzymes of the Entner Doudoroff and pentose phosphate pathways are present in the H. pylori genome, suggesting that glucose can be used as a source of energy. Our study revealed that most genes involved in energy metabolism of H. pylori were up-regulated, which was consistent to other studies (Crapoulet et al, 2006). The increased levels of energy generation indicate that the cells incubated at low temperature are stressed by energy limitation.…”
Section: Helicobacter Pylori Expression Microarray Temperaturesupporting
confidence: 94%
See 1 more Smart Citation
“…Homologues of enzymes involved in the utilization of carbohydrates and enzymes of the Entner Doudoroff and pentose phosphate pathways are present in the H. pylori genome, suggesting that glucose can be used as a source of energy. Our study revealed that most genes involved in energy metabolism of H. pylori were up-regulated, which was consistent to other studies (Crapoulet et al, 2006). The increased levels of energy generation indicate that the cells incubated at low temperature are stressed by energy limitation.…”
Section: Helicobacter Pylori Expression Microarray Temperaturesupporting
confidence: 94%
“…But recently, an increasing number of reports suggest that heat shock proteins can be induced by cold shock, and that the proper folding of proteins, as well as the refolding of cold-damaged proteins, is important for bacterial growth during cold shock (Phadtare et al, 2004;Crapoulet et al, 2006;Lee et al, 2008). Under physiological conditions, DnaK represents the intracellular stress sensor.…”
Section: Helicobacter Pylori Expression Microarray Temperaturementioning
confidence: 99%
“…Vaccine development is unnecessary due to the low prevalence of WD, even taking into account its apparent underdiagnosis [1]. The research of specific markers of WD has been undertaken in the fields of genetics [27], proteomics [28,29] and immunology [30][31][32] (Table 2). …”
Section: Environmental Origin Of T Whipplei and Asymptomatic Carriersmentioning
confidence: 99%
“…Nowadays, the high-throughput transcriptome sequencing (RNA-seq) technique has dramatically accelerated the analytical capacity and has been widely used in constructing global networks of gene expression (16). In the past decades, there were several comparative transcriptome analyses focused on temperature-dependent genes in some important environmental bacteria, including Escherichia coli (12), Tropheryma whipplei (13), Pseudomonas aeruginosa (14), Streptococcus thermophilus (17), and Bacillus cereus (18). The expression patterns of virulence-related genes in Listeria monocytogenes, Salmonella enterica, Xanthomonas oryzae, and V. cholerae have also been revealed through transcriptome analysis (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Hence, temperature has been considered one of the crucial environmental factors that can regulate the metabolic process, growth, adhesion, and even pathogenicity of bacteria by influencing their gene expression (12)(13)(14). V. splendidus strain JZ6 was previously isolated and identified as a pathogenic agent for Yesso scallop (Patinopecten yessoensis) in low-temperature environments (5).…”
mentioning
confidence: 99%